Mid-Miocene Lake Level Fluctuations in the Lunpola Basin, Central Tibetan Plateau - Liang, Yu; Quan, Cheng; Li, Yongxiang; Liu, Weiguo; Liu, Zhonghui (Frontiers in Earth Science, 2021)
Knowledge of paleolake evolution is highly important for understanding the past hydroclimate regime on the Tibetan Plateau and associated forcing mechanisms. However, the hydrological history of paleolakes on the central plateau, the core region of the plateau, remains largely inconclusive. Here we present new biomarker records from lacustrine deposits of the Lunpori section in the Lunpola Basin to reconstruct detailed lake-level fluctuations during the mid-Miocene. A set of n-alkane indexes, including the proportion of aquatic macrophytes (Paq), average chain length (ACL), and carbon preference index (CPI), as well as the content of n-alkanes, vary substantially and consistently throughout the studied interval. Our results altogether show relatively low lake level at ~16.3‒15.5 Ma and high lake level before and after the interval, which is in line with the lithological observations in the section. Further comparison with existing regional and global temperature records suggests that lake level fluctuations can be largely linked to global climatic conditions during the mid-Miocene, with lake expansion during relatively warm periods and vice versa. Therefore, we infer that global climatic changes might have controlled the lake-level fluctuations in this region during the mid-Miocene, whereas the tectonic uplift likely played a subordinate role on this timescale.